2020
DOI: 10.3390/nu12020297
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Muscle-Specific miR-133b and miR-206 Correlate with Nutritional Status and Sarcopenia

Abstract: Sarcopenia and malnutrition are commonly occurring conditions in the elderly that frequently coexist, leading to substantial effects on morbidity/mortality. Evidence established muscle-specific microRNAs (miRNAs) or myomiRs as essential regulators of skeletal muscle processes, from myogenesis to muscle homeostasis. This study aimed to evaluate the association between myomiRs and sarcopenia and explore the potential of nutrition in mediating this association. qPCR was employed to characterize the myomiR-1, -133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 59 publications
2
35
0
4
Order By: Relevance
“…Moreover, Drummond et al (2009) showed that acute essential amino acids (EAAs) ingestion elicited robust increases in miR-1, miR-23a, miR-208b, and miR-499 expression, with an accompanying increase in MyoD1 and Follistatin Like 1 mRNA expression, and a decrease in myostatin and MEF2C mRNA expression in human skeletal muscle [ 52 ]. It has been also reported by Iannone et al [ 58 ] that miR-133a/b and miR-206 appear to be directly or indirectly regulated by the mammalian target of rapamycin (mTOR) [ 59 ], the main mediator of cellular nutrient sensing, and a key regulator of skeletal muscle growth and hypertrophy [ 60 ]. According to these studies, Zhang and al.…”
Section: Nutrition-dependent Microrna Regulation Of Skeletal Musclmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Drummond et al (2009) showed that acute essential amino acids (EAAs) ingestion elicited robust increases in miR-1, miR-23a, miR-208b, and miR-499 expression, with an accompanying increase in MyoD1 and Follistatin Like 1 mRNA expression, and a decrease in myostatin and MEF2C mRNA expression in human skeletal muscle [ 52 ]. It has been also reported by Iannone et al [ 58 ] that miR-133a/b and miR-206 appear to be directly or indirectly regulated by the mammalian target of rapamycin (mTOR) [ 59 ], the main mediator of cellular nutrient sensing, and a key regulator of skeletal muscle growth and hypertrophy [ 60 ]. According to these studies, Zhang and al.…”
Section: Nutrition-dependent Microrna Regulation Of Skeletal Musclmentioning
confidence: 99%
“…It has been reported that the cytokine named TNF-weak-inducer of apoptosis can induce muscle wasting through the regulation of miRNAs including miRNA-1, miRNA-133a, and miRNA133b, involved in the growth of mouse skeletal muscle [ 79 ]. Besides, a down-regulation of miRNA-133b and miRNA-206 was observed by Georgantas et al in the muscle of patients with inflammatory myopathy [ 80 ], and the expression of these miRNAs has been correlated by Iannone et al with the nutritional status, revealing a mediating effect of nutrition on the relationship between sarcopenia and myomiRNAs [ 58 ].…”
Section: Nutrition-dependent Microrna Regulation Of Inflammageingmentioning
confidence: 99%
See 1 more Smart Citation
“…microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are vital non-coding RNAs (ncRNAs). Studies have shown that miRNAs and lncRNAs may be associated with cancer (Ramalho-Carvalho et al, 2017), as well as neurological (Faghihi et al, 2008), cardiovascular (Ponnusamy et al, 2019), and other diseases (Iannone et al, 2020). miRNAs and lncRNAs are also reported to play critical roles in muscle development and other muscle-related diseases, such as skeletal muscle wasting in cachexia (Chen et al, 2006(Chen et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that targeting miR-133b and its close relative, miR-133a, affect different stages of myogenesis, including the proliferation of satellite cells [19,20] and myoblasts [21], the differentiation of satellite cells into either myoblasts or brown adipose tissue [22], and the formation of muscle fibers [20,23,24]. In vivo, published data indicate that skeletal muscles upregulate miR-133b during regeneration following injury [25] and may utilize miR-133b to maintain homeostasis during cellular, functional and biochemical changes induced by exercise [26] and denervation [27] as well as in sarcopenia [28]. Additionally, miR-133b was shown to accelerate muscle regeneration following injury in young adult rats alongside miR-1 and miR-206 [29].…”
Section: Introductionmentioning
confidence: 99%